ANALISIS HUKUM PENYELESAIKAN SENGKETA ADMINISTRASI PERPAJAKAN MELALUI JALUR NON-LITIGASI: Legal Analysis Of Tax Administrative Dispute Resolution Through Non-Litigation Channels - Evangelista, Beverly; Sumaragatha, I Gusti Bagus Sakah (Ganec Swara, 2025)
Tax administrative disputes in Indonesia can be resolved through litigation or non-litigation channels. The non-litigation path, known as Alternative Dispute Resolution (ADR), includes objection and appeal mechanisms aimed at providing efficient, timely, and low-cost dispute resolution. This study analyzes the effectiveness of objections and appeals as non-judicial tax dispute resolution tools and examines the legal status of Tax Assessment Letters (SKP) that have obtained permanent legal force from the perspective of legal certainty. The research employs a normative legal method using statutory and conceptual approaches, relying on secondary data from primary and secondary legal materials. The findings indicate that the objection process lacks independence due to decisions being made by officials within the Directorate General of Taxes, while appeals in the Tax Court are more objective but face challenges in duration and accessibility. Furthermore, although SKPs that have reached inkracht van gewijsde should reflect legal certainty, they remain subject to administrative correction under certain conditions, potentially undermining finality. Therefore, institutional reform, regulatory strengthening, and increased transparency are necessary to ensure justice and legal certainty in tax administration